2009
DOI: 10.1002/pmic.200900541
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and physiological functions of major royal jelly protein 1 oligomer

Abstract: Royal jelly contains numerous components, including proteins. Major royal jelly protein (MRJP) 1 is the most abundant protein among the soluble royal jelly proteins. In its physiological state, MRJP 1 exists as a monomer and/or oligomer. This study focuses the molecular characteristics and functions of MRJP 1 oligomer. MRJP 1 oligomer purified using HPLC techniques was subjected to the following analyses. The molecular weight of MRJP 1 oligomer was found to be 290 kDa using blue native-PAGE. MRJP 1 oligomer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 42 publications
5
82
0
Order By: Relevance
“…A tryptic peptide from apisin showed an identical sequence to the region Gln167-Lys182 of MRJP1 (Kimura et al 2003). Recently, it was revealed that MRJP1 forms an heterooligomeric complex with apisimin, which was suggested to serve as a subunit-joining protein within the MRJP1 oligomer (Tamura et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tryptic peptide from apisin showed an identical sequence to the region Gln167-Lys182 of MRJP1 (Kimura et al 2003). Recently, it was revealed that MRJP1 forms an heterooligomeric complex with apisimin, which was suggested to serve as a subunit-joining protein within the MRJP1 oligomer (Tamura et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Three MRJP1 hypothetical glycosylation sites have been proposed based on its primary structure (Ohashi et al 1997). Another interesting feature of MRJPl is that it is present in monomeric and oligomeric forms in royal jelly (Simuth 2001;Tamura et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the degradation products of MRJP1 were also shown to have immune-stimulatory activities [ The expanding number of functions of the MRJP1 includes its signifi cant infl uence on honey structure. The MRJP1 has propensity for oligomerization, and in honey, it often forms a large, 350 kDa hetero-hexamer, known as apisin [Kimura et al, 1995[Kimura et al, , 1996] with a peptide named apisimin [Bilikova et al, 2002] that serves as a linker between the MRJP1 oligomers [Tamura et al, 2009]. The MRJP1 molecule is highly glycosylated [Kimura et al, 1995[Kimura et al, , 1996.…”
Section: Honey Proteinsmentioning
confidence: 99%
“…MRJP1 is a 55-57 kDa protein as determined by SDS PAGE, and it is present in monomeric and multimeric forms in RJ. 6,7) Apisin is considered to be a multimer that consists of six molecules of monomeric form. 8) It has been reported that a 57-kDa protein derived from MRJP1 decreased in proportion with storage temperature and incubation time.…”
mentioning
confidence: 99%